Care and Transnational Families: Perspectives from Older Adults, Mothers, and Fathers of Peruvian Emigrants - Cavagnoud, Robin (2023)
This article explores the organization of transnational care provided to older people whose one of their children lives abroad. Based on interviews conducted mainly with older mothers, it analyses the articulation between care received locally and at long distance, the practices they provide to care for family members, and their self-care activities to support themselves in an «independent» old age. The findings confirm the central role of families, particularly of women in ensuring a welfare regime for the older adult population and mitigate the effects of social unprotection.